2006
DOI: 10.1038/sj.emboj.7601476
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome substrate degradation requires association plus extended peptide

Abstract: To determine the minimum requirements for substrate recognition and processing by proteasomes, the functional elements of a ubiquitin-independent degradation tag were dissected. The 37-residue C-terminus of ornithine decarboxylase (cODC) is a native degron, which also functions when appended to diverse proteins. Mutating the cysteine 441 residue within cODC impaired its proteasome association in the context of ornithine decarboxylase and prevented the turnover of GFP-cODC in yeast cells. Degradation of GFP-cOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
135
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(150 citation statements)
references
References 31 publications
15
135
0
Order By: Relevance
“…In addition to requiring a mechanism for binding to the proteasome, the efficient degradation of proteasomal substrates can involve poorly structured regions in their termini, from which unfolding or degradation is initiated (Prakash et al, 2004;Takeuchi et al, 2007). During ubiquitin-independent degradation of the enzyme ornithine decarboxylase, both these requirements are supplied by a stretch of 37 C-terminal residues (Takeuchi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to requiring a mechanism for binding to the proteasome, the efficient degradation of proteasomal substrates can involve poorly structured regions in their termini, from which unfolding or degradation is initiated (Prakash et al, 2004;Takeuchi et al, 2007). During ubiquitin-independent degradation of the enzyme ornithine decarboxylase, both these requirements are supplied by a stretch of 37 C-terminal residues (Takeuchi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…During ubiquitin-independent degradation of the enzyme ornithine decarboxylase, both these requirements are supplied by a stretch of 37 C-terminal residues (Takeuchi et al, 2007). Like ornithine decarboxylase, Fra-1 contains a 30-40 residue long C-terminal region (DEST domain) that is poorly structured .…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination by itself does not always lead to rapid degradation [30,31] and effective proteolysis of a folded protein requires the presence of an unstructured region in the substrate [32,33], either at the ends of the polypeptide chain or internally [32,34]. The unstructured regions serves as the degradation initiation site and proteolysis continues from there along the polypeptide chain.…”
Section: A Second Step In Ubiquitin-dependent Proteasome Targetingmentioning
confidence: 99%
“…During activation, the IκB is degraded by the proteasome without affecting the other subunits of NFκB [46]. The explanation for these observations seemed to be that degradation begins specifically at the ubiquitination site but we now know that this mechanism may not always apply [32,33]. It will be interesting to determine whether the two components of the targeting signal could work together when separated onto two different polypeptides chains in a complex.…”
Section: A Second Step In Ubiquitin-dependent Proteasome Targetingmentioning
confidence: 99%
“…It was also observed that susceptibility to proteasomal degradation is affected by structural elements near the degradation sites (19). Additionally, the presence of an unstructured region can initiate the unfolding step and greatly facilitates the degradation process (28,29).…”
mentioning
confidence: 99%